INTERNET MEDIA IN THE MODERN INFORMATION SPACE OF UKRAINE: SOCIO-LEGAL ASPECTS - Pakhnin , M.; Germanova, Y. (Pressing Problems of Public Administration, 2019)
The role and the place of Internet media in the processes of modern information space of Ukraine formation is defined. The communicative aspects of “new” and “traditional” media interaction in the perspective of a single information space development are considered. The influence of the Internet on a mass communication development has been determined. The fundamental issues of regulation of modern Internet media by public authorities have been formed.The relevance of scientific research of an Internet media as the basic tool in political, social and public administration is determined. The features of modern Internet media are determined: feedback; transparency; mass advertising; User Generated Content; discussions in the comments to the mass media messages; lack of censorship; low level of financial threshold barrier; real time content creation (for example, text broadcasts of events); hypertextuality; usage of social networks as platforms for content ptomotion and more. The principles of information openness of Internet media are considered as the basic factor of creation and implementation of the state information policy. Issues of regulation of Internet media needs special attention in the context of the current factual information war against Ukraine.